Peningkatan Keterampilan Berpikir Tingkat Tinggi Ipa Melalui Model Pembelajaran Discovery Learning - Suhartati Suhartati (Jurnal Lingkar Mutu Pendidikan, 2021)
Higher order thinking skills (HOTS) are thinking processes that connect, manipulate, transform knowledge and experience to solve problems in new situations. The research conducted aims to improve high-order thinking skills (HOTS) in the content of science lessons through the discovery learning model for fourth grade students of SD Negeri Bleber 1 in the 2019/2020 school year. The subjects of this study were fourth grade students of SD Negeri Bleber 1 Prambanan having their address at Karanggede, Sumberharjo, Prambanan, Sleman, Yogyakarta Special Region. The type of research used is Classroom Action Research which lasts for two cycles, each cycle having two meetings. The data collection instruments used were direct observation and written tests. The data analysis technique used is descriptive analysis of improving science learning outcomes. The way to improve higher-order thinking skills is done by applying the discovey learning model. The learning implementation is based on the discovey learning cycle, namely giving, identifying problems, collecting data, processing data, and drawing conclusions. The average pre-test learning outcomes of science subject content class 55. In the first cycle the average science subject content class increased to 70. In the second cycle the average science subject content class increased to 80. The results of pre-test learning completeness were the number of students who completed as many as 8 students (29%). In the first cycle, the number of students who completed increased by 9 students (31%) to 17 students (60%). In cycle II, the number of students who completed increased by 7 students (26%) to 24 (86%). This shows that the implementation of the discovery learning model can improve the high-level thinking skills of fourth grade students at SD Negeri Bleber 1 Prambanan for the 2019/2020 school year.